2015
DOI: 10.1177/0021934715600964
|View full text |Cite
|
Sign up to set email alerts
|

“Our Ancestors Were Material Scientists”

Abstract: The quest for a comprehensive understanding of Africa's indigenous technology has been an important intellectual agenda in Black Studies. In some instances this interest has tended to be speculative and derivative because most Black Studies scholars are not trained in the disciplinary fields that are relevant for investigating Africa's indigenous technology through primary field and laboratory research. Collaboration between Black Studies scholars and those in the physical sciences is therefore important in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The glass produced there had a very specific composition, i.e. high lime high alumina glass (HLHA), which is not produced anywhere else in the world [5][6][7][8]. In sub-Saharan Africa, glass beads were therefore mostly exotic items, traded in various quantities through diverse longdistance exchange routes.…”
Section: Background: the Production And Trade Of Glassmentioning
confidence: 99%
“…The glass produced there had a very specific composition, i.e. high lime high alumina glass (HLHA), which is not produced anywhere else in the world [5][6][7][8]. In sub-Saharan Africa, glass beads were therefore mostly exotic items, traded in various quantities through diverse longdistance exchange routes.…”
Section: Background: the Production And Trade Of Glassmentioning
confidence: 99%
“…Our data are also consistent with the result of Ige's (2012: 489) experimental work, which demonstrated that a mixture of feldspar-rich sand and snail shell, when melted in small crucibles at temperatures above approximately 700°C, indeed produces glass with a composition similar to the Ile-Ife HLHA. Archaeological work at Osogbo has uncovered a feldspar-rich substance suggested to have been used in glassmaking during the early period in Osogbo in the seventeenth century AD (Ogundiran & Ige 2015), demonstrating the longevity and geographic spread of this technology and perhaps its disappearance and reinvention. This feldspar-lime glass has no parallel in pre-modern glassmaking, decisively confirming the autonomous origin of the Ile-Ife glassmaking technology.…”
Section: Implications and Concluding Remarksmentioning
confidence: 99%
“…It has also been demonstrated that HLHA glass beads were manufactured on a large scale, suggesting access to a ready market and high demand for the product during the classical era of Ile-Ife (Babalola 2019). Recent work has identified very similar bead-making evidence from early Osogbo, some 45km north of Ile-Ife and dating to a few centuries later (Ogundiran & Ige 2015). While significant work has been undertaken on the production of glass beads in classical Ile-Ife and seventeenth-century AD Osogbo, it is nowhere near complete, and further investigations are needed, especially in the wake of the discovery of what appeared to be semi-finished glass.…”
Section: Introductionmentioning
confidence: 99%